Poemi sacri nel Seicento italiano - Samarini, Francesco (Verbum – Analecta Neolatina, 2014)
A large number of religious poems were published in Italy during the 17th century, but these works have often been ignored by critics. The authors of the compositions aimed at replacing the traditional “escapist” literature – the books of chivalry in particular – with a pious form of entertainment. The translations of the Scriptures in vernacular were prohibited by the Church, therefore this kind of poetry was one of the few ways to get in contact with the Scriptures for the readers who did not know Latin. The plots of these poemswere drawn directly either fromthe Bible or fromhagiographies, although their stories were enriched with new episodes invented by the writers, who usually showed the tendency to imitate Torquato Tasso’s Gerusalemme liberata. This paper intends to give a general description – with some relevant examples – of this complex literary genre, which is little known but extremely rich and various.